The Told and Retold Story of Romanian Accounting - Iulia Jianu; Ionel Jianu (Journal of Accounting and Management Information Systems (JAMIS), 2012)
This article offers an image of the consequences that have arisen in the accounting practice in Romania, as a result of frequent changes in Romanian accounting in the recent years. In order to achieve this objective, it was conducted a positive type research by applying a survey among the accounting and consultancy companies in Romania. The results of this study are the following: in the Romanian accounting practice, the fiscal reasoning dominates the economic reasoning in recognizing the economic and financial transactions; the accounting regulations harmonized with the European accounting directives have been favorably received by professional accountants in Romania; Romanian professional accountants are trained to apply the IAS/IFRSs; entities consider that the benefits of implementing the IAS/IFRSs justify the difficulties involved in their application.
Keywords: M41; M48; 650; Romanian accountant; Romanian accounting; consultancy companies; IAS/IFRS enforcement